Post Operative Complications of Non-Traumatic Ileal Perforation in Patients Undergoing Emergency Laparotomy - Saddiqe, Hazrat Abu Bakar; Arif, Ata Ullah; Zaman, Ahmed; Aslam, Farhan; Fawad Ullah; Sahibzada Saad ur Rehman (Indus Journal of Bioscience Research, 2025)
Background: Intestinal perforation is still a serious surgical emergency and can be caused by enteric fever, intestinal tuberculosis, or inflammatory bowel disease. Subsequent leakage into the peritoneal space causes peritonitis, sepsis, and considerable mortality if not attended to immediately. Emergency laparotomy is still considered a lifesaving intervention, but postoperative sequelae still pose considerable morbidity, especially in limited settings such as Peshawar. Objective: To find out the frequency of post-operative complications of non-traumatic ileal perforation in patients undergoing emergency laparotomy at our health setup. Study Design: Descriptive cross-sectional study. Duration and Place of Study: Conducted from December 2024 to May 2025 in the Department of Surgery, Lady Reading Hospital, Peshawar. Methodology: A total of 133 patients aged 18–40 years with confirmed non-traumatic ileal perforation were included through consecutive sampling. All underwent emergency laparotomy and were observed for complications including wound infection, peristomal excoriation, wound dehiscence, prolonged ileus, and fistula formation for up to 45 days post-surgery. Results: The mean age was 28.36 ± 6.73 years with 62.4% males. Enteric fever accounted for 62.4% of perforations, followed by tuberculosis (26.3%) and adhesions (11.3%). Wound infection occurred in 31.6%, peristomal excoriation in 17.3%, wound dehiscence in 10.5%, and prolonged ileus and fistula formation each in 3% of patients. Conclusion: Postoperative complications following emergency laparotomy for non-traumatic ileal perforation are common, with wound infection being the predominant issue.